Pengaruh Motivasi Kerja dan Lingkungan Kerja Fisik Terhadap Kinerja Karyawan pada PT Geo Dipa Energi (Unit Patuha) Kabupaten Bandung - Manihuruk, Dominicus Celvin Parulian; Saragih, Romat (eProceedings of Management, 2024)
This research aims to determine the effect of work motivation and the physical work environment on employeeperformance at PT Geo Dipa Energi (Patuha Unit) both partially and simultaneously, as well as to find out how workmotivation, physical work environment and employee performance at PT Geo Dipa Energi (Patuha Unit) ). Theprimary data obtained were 85 respondents who were employees of PT Geo Dipa Energi (Unit Patuha) BandungRegency by sampling using the saturated sampling method. Based on the analysis results, it shows that workmotivation is included in the good category, the physical work environment is included in the good category andemployee performance is included in the good category. The results of hypothesis testing show that work motivationand the physical work environment have a significant effect on employee performance, both partially andsimultaneously.Keywords-work motivation, physical work environment, employee performance